Impact of the Dipole Tilt Angle on the Ionospheric Plasma as Modeled with IPIM. Issue 6 (8th June 2020) - Marchaudon, A.; Blelly, P.‐L.
Abstract: We ran the IRAP Plasmasphere Ionosphere Model (IPIM) for several flux tubes at different distances from Earth for very quiet conditions, in order to model the convection and corotation transport of closed flux tubes in the plasmasphere for tilted/eccentric dipolar magnetic field configuration and for solstice and equinox conditions. For each simulation, the model was run for 30 days in order to study the long‐term evolution of the plasmasphere‐ionosphere system. The goal is to study the combined effect of corotation and convection, which causes eventually a lag of the flux tube motion with respect to the Earth. This combination of nonuniform rotation and subcorotation in average becomes important especially in the outer plasmasphere and causes nonuniform drift of the dipole tilt projection in the plane of the flux tube with time, changing drastically the plasma distribution along this flux tube. In the classical representation of the plasmasphere, the ionosphere only depends on angular Magnetic Local Time (MLT) sector. We show that due to the tilt effect, solar illumination along the flux tube and field‐aligned transport varies from one day to the other and causes also a day‐to‐day variation in the plasma distribution along the tube. This effect implies that a stable representation of the plasmasphere in MLT during quiet conditions is an erroneous view, and no real dynamic equilibrium can be reached, in particular close to the stagnation point. Key Points: Combined corotation and convection in the plasmasphere causes nonuniform drift of the dipole tilt projection in the flux tube plane Dipole tilt projection's variation causes variable solar illumination along the tube and day‐to‐day variation in plasma distribution Even for very quiet conditions no equilibrium can be reached in the plasmasphere due to day‐to‐day variation in the tube plasma distribution